2010
DOI: 10.1210/me.2009-0421
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Androgen-Responsive Transcription by the Chromatin Remodeling Factor CHD8

Abstract: The androgen receptor (AR) mediates the effect of androgens through its transcriptional function during both normal prostate development and in the emergence and progression of prostate cancer. AR is known to assemble coactivator complexes at target promoters to facilitate transcriptional activation in response to androgens. Here we identify the ATP-dependent chromatin remodeling factor chromodomain helicase DNA-binding protein 8 (CHD8) as a novel coregulator of androgen-responsive transcription. We demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 55 publications
4
43
0
Order By: Relevance
“…5A). In line with these findings, modulation of the AR-mediated transcription was recently reported for CHD8, another member of the CHD family (16). To test whether this effect was due to the impaired recruitment of AR to the promoters of AR-responsive genes, we carried out ChIP analysis and determined the AR occupancy at responsive promoters (PSA, TMPRSS2, FKBP5, ELK4, and KLK2) in control and CHD1-depleted LNCaP cells upon stimulation with DHT.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…5A). In line with these findings, modulation of the AR-mediated transcription was recently reported for CHD8, another member of the CHD family (16). To test whether this effect was due to the impaired recruitment of AR to the promoters of AR-responsive genes, we carried out ChIP analysis and determined the AR occupancy at responsive promoters (PSA, TMPRSS2, FKBP5, ELK4, and KLK2) in control and CHD1-depleted LNCaP cells upon stimulation with DHT.…”
Section: Resultssupporting
confidence: 54%
“…CHD5 is a known tumor suppressor controlling apoptosis via the p19-p53 pathway and which is often inactivated by deletions involving the chromosomal band 1p36 (14,15). Furthermore CHD8, another member of the CHD gene family, has been suggested to play a role in androgen receptor (AR)-dependent transcription regulation in prostate cancer (16).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, LNCaP cells were grown in phenol red-free RPMI-1640 medium with 10% FBS (charcoal stripped) for 3 d and treated with 1 nM R1881 or vehicle for 24 h. Prepared chromatin was immunoprecipitated with anti-AR or anti-IgG antibody at 4°C overnight. The precipitated DNA was PCR amplified with primers corresponding to PSA enhancer or corresponding to the androgen-responsive elements of TMPRSS2, as previously described (25,26). The relative enrichment was shown using agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…The COOH-terminal region of full-length CHD8 (CHD8 L ) interacts with the insulator-binding protein CTCF, with this interaction being important for insulator activity (14). CHD8 has also been implicated as a positive or negative transcriptional regulator of various genes (19,32,33,45,46). We previously showed that Chd8 ÏȘ/ÏȘ mice die early during embryogenesis, manifesting widespread apoptosis (28), whereas additional deletion of the tumor suppressor gene p53 ameliorated this developmental arrest (29).…”
mentioning
confidence: 99%